PENGEMBANGAN SISTEM INFORMASI MANAJEMEN KEUANGAN UNTUK PENGELOLAAN DATA MANAJEMEN KEUANGAN PADA KELOMPOK BATIK WUKIRSARI - Putri Rachmawati Rachmawati (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2018)
Information System is a tool of human in storing, processing, and organizing data. Sophistication of information systems will accelerate the processing and management of data. The purpose of developing information systems that will be used in SMEs (Small and Medium Enterprises) can be used to develop an effective and efficient system. , quality, effectiveness, efficiency and timeliness by seeing great results very high The results of the effectiveness of information with financial statements, income reports, can be increased by the community 30%. very easy in the use of 70% . The results achieved is the access database applications and websites as information needed by people in need. ar on the performance of Wukirsari batik group community.